EVALUASI KELAYAKAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA PADA MATA KULIAH TP. KEPELATIHAN BULUTANGKIS - Ariani, Luh Putu Tuti; Marti, Ni Wayan (Universitas Pendidikan Ganesha, 2022)
Badminton is a complex game that uses a racket as a striking tool and a shuttlecock as an object. Badminton has basic techniques that must be taught so that players have good technical quality of the game. This study aims to tempt the feasibility of the learning media for the basic techniques of badminton and determine the feasibility level of the learning media. The data collection method used is by making research instruments to test large groups and small groups. Instruments will be given to students who take part in the feasibility test process for learning media for the basic techniques of badminton. In this study, the average results of field trials as a whole with a percentage of 93%, so it can be concluded that interactive media are the basic techniques of multimedia-based badminton games that are implemented in TP. The badminton training developed is feasible and effective because it shows interest, motivation, and helps the accuracy of the media in the use and presentation of basic badminton techniques in the lecture process so that learning objectives are achieved.